Challanges of building information modelling (BIM) in project implementation - Loh, Mei Yee (2014)
Building Information Modelling (BIM) is a technology that is currently gaining momentum within the construction industry as interoperability issue is become more and more important in relative to the quality and productivity of the industry. BIM is defined as a modelling technology and associated set of processes to produce, communicate, and analyze building models throughout the entire project's lifecycle. Although there is bound of benefits that gained from the BIM application, the local construction industry still reluctant to deploy the technology in delivery its services. The objectives of the study is to identify the types of challenges and also investigate the effect of challenges to the outcome of BIM if BIM has being adopted in the local construction industry. The survey questionnaires were distributed in the construction field within Kuantan region. The method of data collection is by questionnaire and also interview. The main conclusion drawn from the study are that the high level of ICT usage among the construction professionals has make the industry more readily in emerging BIM and the identified barriers can confined into three main categories: people, technology and process. Furthermore, the research has identified the potential factors that driven the adoption of BIM and also the consequences of mandating BIM adoption in the local industry.